2015
DOI: 10.4238/2015.july.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-inducing effects of betamethasone on human glioma cell line U251

Abstract: ABSTRACT. We studied the differentiation-inducing effect of betamethasone on human glioma cell line U251 cultured in vitro, and the underlying mechanism. U251 cells were divided into two groups: control group cells, cultured in Dulbecco's Modified Eagle's medium containing 10% fetal bovine serum; and medication group cells, treated with 15 μM betamethasone. Morphological cell changes were observed by inverted microscope, cell cycle changes were ascertained by flow cytometry, and vimentin expression was checked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Although being aware of the differences between primary β-cells and the NOD-derived NIT-1 cell line, it was not technically feasible to obtain islets of Langerhans from newborn pups. The results demonstrated that betamethasone deteriorated NIT-1 cell viability and arrested cell growth, thus preventing the exponential growth phase, as described in other cell lines 39,40 . This effect fits well with the decrease of C-peptide secretion caused by betamethasone, as indirect biomarker of insulin secretion, and with the described effect of synthetic glucocorticoids in islet β-cells, causing a reversible inhibition of insulin secretion 41 but maintaining insulin synthesis.…”
Section: Discussionsupporting
confidence: 57%
“…Although being aware of the differences between primary β-cells and the NOD-derived NIT-1 cell line, it was not technically feasible to obtain islets of Langerhans from newborn pups. The results demonstrated that betamethasone deteriorated NIT-1 cell viability and arrested cell growth, thus preventing the exponential growth phase, as described in other cell lines 39,40 . This effect fits well with the decrease of C-peptide secretion caused by betamethasone, as indirect biomarker of insulin secretion, and with the described effect of synthetic glucocorticoids in islet β-cells, causing a reversible inhibition of insulin secretion 41 but maintaining insulin synthesis.…”
Section: Discussionsupporting
confidence: 57%